2020
DOI: 10.1039/d0nr04592f
|View full text |Cite
|
Sign up to set email alerts
|

A versatile UCST-type composite microsphere for image-guided chemoembolization and photothermal therapy against liver cancer

Abstract: Development of novel chemoembolization agents to improve the treatment efficacy of transarterial chemoembolization (TACE) against liver cancer remains an urgent need in clinical practice. Herein, a versatile composite microsphere with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…The main organs have been dissected and fastened to the histopathological analysis using 10% of formalin embedded in paraffin, cut and stained by Hematoxylin and Eosin (H&E) for standard technology. Pictures were obtained with an optical microscope after staining (Sherwani et al., 2015 ; Guo et al., 2019 ; Park et al., 2019 ; Huang et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The main organs have been dissected and fastened to the histopathological analysis using 10% of formalin embedded in paraffin, cut and stained by Hematoxylin and Eosin (H&E) for standard technology. Pictures were obtained with an optical microscope after staining (Sherwani et al., 2015 ; Guo et al., 2019 ; Park et al., 2019 ; Huang et al., 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that the hyperthermia effect yielded by PNIPAM@GO microspheres in aqueous under NIR irradiation could reach to the required temperature for eliminating tumor cells. 37 To explore the synergistic anti-tumor activity, we encapsulated DOX and 5-FU into PNIPAM core and GO shell respectively, to obtain the predesigned dual-drug loaded PNIPAM@GO microspheres. As above mentioned, the core-shell microspheres displayed excellent photothermal conversion performance under NIR irradiation, thus the thermosensitive PNIPAM cores would shrink in volume upon heating (>32 C) when exposure to NIR, thereby squeezing the loaded DOX out of PNIPAM cores at Stage 1.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve the preset therapeutic temperatures such as room temperature (25°C), body temperature (37°C) and higher temperature (49.9°C), the laser current should be adjusted to meet the heating requirement of PNIPAM@GO microspheres in aqueous, as shown in Figure 4d. It is worth noting that the hyperthermia effect yielded by PNIPAM@GO microspheres in aqueous under NIR irradiation could reach to the required temperature for eliminating tumor cells 37 …”
Section: Resultsmentioning
confidence: 99%
“…The same group later demonstrated that such effects could be intensified by pretreatment with an injection of a vascular disruptor called combretastatin A4-phosphate [63]. Huang et al demonstrated that the combination of therapies with DOX-loaded microspheres containing PDA-functionalized SPIONs improved drug release when a certain temperature threshold was surpassed [64]. Strikingly, PTT/TACE therapy was shown to overcome chemoresistance in HCC cells in vitro by using regular HepG2 cells and chemo-resistant HepG2/ADR cells.…”
Section: Hepatocellular Carcinoma Hepatocellular Carcinoma: Mfhmentioning
confidence: 99%